Mix design and mechanical properties of oil palm shell lightweight aggregate concrete: a review - Shafigh, P.; Jumaat, Mohd Zamin; Mahmud, H. (Academic Journals, 2010)
To build environmentally sustainable structures, especially in developing countries, the possibility of using some agricultural wastes and industrial by-products from different industries as construction materials will be highly desirable and has several practical and economic advantages. Oil palm shell (OPS) is a form of agricultural solid waste in the tropical regimes. Research over the last two decades shows that OPS can be used as a lightweight aggregate for producing structural lightweight aggregate concrete. The density of OPS concrete is around 20 - 25 lower than normal weight concrete. Generally, mechanical properties of OPS concrete are slightly lower than the other types of lightweight aggregate concrete. It seems that from the summary and analysis of the existing information concerning OPS concrete and comparing it with other lightweight aggregate concrete it appears that significant achievements can be attained.